Interactive Learning Media Innovation to Understand the Six Continents of the World in Grade 6 Elementary School Students - Desi Tri Lestyo Pamungkas; Supianto Supianto; Eka Budhi Santosa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Learning about the six continents of the world for sixth-grade elementary school students often encounters challenges in terms of spatial understanding and student interest in the material. This study aims to: 1) Identify the low level of student understanding of the six continents due to the continued use of conventional teaching approaches; 2) Explore strategies used to improve student understanding; and 3) Examine the impact of interactive media innovations on students’ comprehension of the six continents. The method used is a descriptive qualitative approach with a case study method to analyze the application of interactive learning media in improving sixth-grade elementary students' understanding of the six continents. The results show: 1) Students' comprehension of the six continents remains low when teachers rely heavily on conventional methods such as lectures and textbook memorization 2) ) Innovative learning using interactive media serves as an alternative solution to enhance student comprehension; and 3) The use of interactive media led to an increase in students' average scores, with most initially not meeting the minimum passing grade (MPG) on the pre-test, improving to above the KKM on the post-test. Based on these findings, interactive media has proven effective in enhancing learning engagement and effectiveness, as it provides more concrete visual experiences and simulations.